2022
DOI: 10.3390/rs14122947
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Potential Impacts on Regional Climate Due to Land Surface Changes across Mongolia Plateau

Abstract: Although desertification has greatly increased across the Mongolian Plateau during the last decades of the 20th century, recent satellite records documented increasing vegetation growth since the 21st century in some areas of the Mongolian Plateau. Compared to the study of desertification, the opposite characteristics of land use and vegetation cover changes and their different effects on regional land–atmosphere interaction factors still lack enough attention across this vulnerable region. Using long-term tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Changes in air temperature, the most prominent climate parameter, will indirectly have the most significant impact on vegetation growth. These changes are especially evident in sensitive areas of arid and semi-arid regions [36]. For example, in 2000, when the air temperature increased, the amount of precipitation decreased, and in the years 2010 and 2020, when the precipitation increased, the amount of vegetation cover increased in the basin, especially in the years when the NDVI and EVI values were high.…”
Section: Discussionmentioning
confidence: 99%
“…Changes in air temperature, the most prominent climate parameter, will indirectly have the most significant impact on vegetation growth. These changes are especially evident in sensitive areas of arid and semi-arid regions [36]. For example, in 2000, when the air temperature increased, the amount of precipitation decreased, and in the years 2010 and 2020, when the precipitation increased, the amount of vegetation cover increased in the basin, especially in the years when the NDVI and EVI values were high.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when discussing the response of vegetation to climate change, this study does not consider the feedback effect of vegetation on climate, and our previous studies show that the feedback effect of vegetation change on regional climate is strong, which may affect the results of this paper, Yu L. X. et al ( 2020) determined the response of vegetation change to climate by using a high-resolution land atmosphere coupled regional climate model, and found that the northern part of northern China showed obvious cooling, including the Northeast Plain, the Loess Plateau and the eastern part of the arid and semi-arid areas in the north (Yu L. X. et al, 2020). Li et al (2022) used a long time series multi-source satellite and a high-resolution land-air coupled regional climate model (WRF) to investigate the climate feedbacks of surface changes observed in the Mongolian Plateau from the 1990s to the 2010s. According to model simulations, vegetation greening produces a local cooling effect, while vegetation degradation produces a warming effect (Li et al, 2022).…”
Section: Uncertainties and Future Workmentioning
confidence: 96%
“…Li et al (2022) used a long time series multi-source satellite and a high-resolution land-air coupled regional climate model (WRF) to investigate the climate feedbacks of surface changes observed in the Mongolian Plateau from the 1990s to the 2010s. According to model simulations, vegetation greening produces a local cooling effect, while vegetation degradation produces a warming effect (Li et al, 2022). Liu et al (2022) used multi-source satellite measurements records and a high-resolution land atmosphere coupled regional climate model (WRF) to investigate the land surface changes and their associated thermal and wet effects in three major ecosystems in the Heilong-Amur River basin from 1982 to 2018, highlighting the different surface responses and feedbacks of different ecosystems to climate change, depending on the specific vegetation variation and background climate, which may lead to warming/cooling and wetting/drying effects (Liu et al, 2022).…”
Section: Uncertainties and Future Workmentioning
confidence: 99%
See 1 more Smart Citation